2021
DOI: 10.21660/2021.80.j2033
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of Refractory Brick From Locally Available Red Clay Blended With White Portland Cement and Its Performance Evaluation

Abstract: In this paper, refractory bricks were developed by using locally obtainable materials like red clay and glass sand in Bangladesh. The Preliminary investigation was conducted by measuring the compressive strength of bricks produced by adding a range of materials with red clay in different proportions. It was found that the brick containing 30% white Portland cement and 10% glass sand with red clay (60%) demonstrated the highest compressive strength (36.20 mpa). The suitability of refractory bricks was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A large number of refractory materials are made from naturally occurring high-melting-point oxides or compounds, like dolomite, chromite-magnesite, zirconia, aluminosilicate, carbon, and magnesia. Fireclay, a type of aluminosilicate refractory material, is one of the preferred refractory materials due to its availability (Samad et al, 2021). Clays are hydrated silico-aluminous minerals with a stacking of two different types of layers that contain silicon in tetrahedral coordination and aluminum in an octahedral environment, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of refractory materials are made from naturally occurring high-melting-point oxides or compounds, like dolomite, chromite-magnesite, zirconia, aluminosilicate, carbon, and magnesia. Fireclay, a type of aluminosilicate refractory material, is one of the preferred refractory materials due to its availability (Samad et al, 2021). Clays are hydrated silico-aluminous minerals with a stacking of two different types of layers that contain silicon in tetrahedral coordination and aluminum in an octahedral environment, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Red clay brick was used as an additive material to develop refractory bricks in Bangladesh. It is found that refractory bricks with 60% red clay bricks have the highest compressive strength value [22].…”
Section: Literature Reviewmentioning
confidence: 97%
“…In addition, refractory materials can be categorised on the of basis chemical features such as acid, basic and neutral products. The increase in silica in a batch formulation the increase the acidity properties [3]. The amount of global of refractories consumption in the steel industry was approximately 27 million tons/year.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of refractory are produced from geological high melting point oxides or compounds such as, alumina, carbon, magnesia, zirconia, aluminosilicate, silica, dolomite, chrome-magnesite. Among the favoured refractory material due to availability is the fireclay, which is category of aluminosilicate refractory materials [3]. Clays are hydrated silico-aluminous minerals whose structure is made up of a stacking of two types of layers containing, respectively, aluminium in an octahedral environment and silicon in tetrahedral coordination.…”
Section: Introductionmentioning
confidence: 99%